The Interpretation of ta hagia in Hebrews 9:8 - JUAS, JEFFIENUS (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2024)
The Greek word ta hagia in Hebrews 9:8 is semantic in nature. Many scholars agreed to some extent that there is indeed a disagreement among the modern English translation of the Bible in translating the word ta hagia in Hebrews 9:8. Some modern translations, translate it as “Most Holy Place”, some translate it as “sanctuary” and some even translate it as “Holy Place”. This paper clarifies the importance on looking on the grammatical categories of the word ta hagia and its immediate context to determine the correct translation for ta hagia which is a study that involves both lexical and literary contextual analysis. From the study, the Researcher found out that ta hagia should be translated as “sanctuary” or “holy places” in Hebrews 9:8.